Myths and Common Misbeliefs About Colorectal Cancer Causation in Palestine: A National Cross-Sectional Study - Mohamedraed Elshami; Shoruq Ahmed Naji; Mohammad Fuad Dwikat; Ibrahim Al-Slaibi; Mohammed Alser; Mohammed Ayyad; Balqees Mustafa Mohamad; Wejdan Sudki Isleem; Adela Shurrab; Bashar Yaghi; Yahya Ayyash Qabaja; Fatma Khader Hamdan; et al. (JCO Global Oncology, 2024)
PURPOSETo explore public awareness of myths around colorectal cancer (CRC) causation in Palestine and to examine factors associated with good awareness.MATERIALS AND METHODSConvenience sampling was used to recruit adult Palestinians from governmental hospitals, primary health care centers, and public spaces. Recognizing 13 myths around CRC causation was assessed using a translated-into-Arabic version of the Cancer Awareness Measure-Mythical Causes Scale. Awareness level was determined based on the number of CRC mythical causes recognized: poor (0-4), fair (5-9), and good (10-13). Multivariable logistic regression was used to examine the association between sociodemographic characteristics and displaying good awareness. It adjusted for age group, sex, education, occupation, monthly income, residence, marital status, having chronic diseases, being a vegetarian, knowing someone with cancer, and site of data collection.RESULTSOf 5,254 participants approached, 4,877 agreed to participate (response rate, 92.3%). A total of 4,623 questionnaires were included in the final analysis: 2,700 from the West Bank and Jerusalem (WBJ) and 1,923 from the Gaza Strip. Only 219 participants (4.7%) demonstrated good awareness of myths around CRC causation. WBJ participants were twice more likely than those from the Gaza Strip to display good recognition (5.9% v 3.1%). Male sex, living in the WBJ, and visiting hospitals were all associated with an increase in the likelihood of displaying good awareness. Conversely, knowing someone with cancer was associated with a decrease in the likelihood of displaying good awareness. Having a physical trauma was the most recognized CRC causation myth (n = 2,752, 59.5%), whereas eating food containing additives was the least (n = 456, 9.8%).CONCLUSIONOnly 4.7% displayed good ability to recognize myths around CRC causation. Future educational interventions are needed to help the public distinguish the evidence-based versus mythical causes of CRC.